Application of large-scale particle image velocimetry to entrance flows - Fakhri, Alireza, author; Ettema, Robert, advisor; Thornton, Christopher, committee member; Bond, Laurel, committee member (Colorado State University. Libraries, 2021)
This thesis presents the findings of the application of Large-Scale Image Velocimetry (LSPIV) to illuminate three entrance flows. LSPIV is an image-based method that non-invasively measures two-dimensional instantaneous free-surface velocities of water flow using video equipment. Three different applications used in this study are a flume study with three different contraction ratios, flow through and over spillways in hydraulic models for Gross Dam and Los Vaqueros Dams. For the first application, large-scale-particle velocimetry (LSPIV) was applied to estimate the top-width of the vena contracta formed by an approach open-channel flow entering a contraction of the channel. The experiments investigated the requisite dimensions of two essential LSPIV components: the Search Area and Interrogation Area, to establish the optimum range of these components for use in LSPIV application to contractions of open-channel flows. Of practical concern (e.g., bridge hydraulics) is flow contraction and contraction scour that can occur in the vena contracta region. The thesis showed that optimum values for the Search Area (SA) and Interrogation Area (IA) were 10 and 60 pixels, respectively. Also, the study produced a curve indicating a trend for vena-contracta width narrowing with a variable ratio of approach-channel and contracted-channel widths and varying bed shear stress of approach flow. For the other two applications, the hydraulic models of the spillways for Gross Dam and Los Vaqueros Dam, LSPIV was applied to assess the robustness of LSPIV on mapping the streamlines through and over spillways.
Keywords: interrogation area; LSPIV parameters; vena contracta width; LSPIV; contracted open channels; search area